The Activeness of Women Follow the Arisan Group (Case Study in Groups of Community Arisan and Groups of Professional Arisan) - NOVITA, NOVITA; YATI, HADIYATI (Human Sustainability Procedia, 2018)
The phenomenon of women’s role is getting more attention in our community right now. Women become the successful source in all fields but the women’s role itself was not respected or was not valued by people in ourcommunity. The basis of this motivation will be an effort to build the role of women to be more empowered and real in women’s institutions. Problems come in groups of women who held social activities such as social gathering which are the issue of activeness in following various activities, less brave to appear in front of people or lack of confidence as well as lack of motivation due to lack of support from family, colleagues and the surrounding environment. This research focuses on the variables of socialization pretension and the interest to save money. This research question is about what are the factor that makes women are motivated to follow arisan and become active in groups of arisan. Through the survey method, the questionnaires distributed to two groups of arisan (social gathering) women which are the arisan groups in the community and the professional arisan group. The sample is about 31 respondents taken purposively and analyzed quantitatively using SEM warpPLS. The result of the research shows that socialization becomes the motivating factor of women joining social gathering but not the factor that make the women active in joining the arisan either directly or indirectly. While the pretension factor to save money is a factor that makes women actively follow the arisan but not a factor that motivates women to join arisan. Motivation to follow the arisan (social gathering) did not also make women active in arisan activities